The Influence of Servant Leadership on Employee Performance and Organizational Commitment: The Mediating Effect of Work Motivation - Isbat; Nancy Yusnita; Widodo Sunaryo; Yayan Hadiyat (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This research examines how servant leadership influences employee performance and organizational commitment within the Indonesian public sector, with work motivation as a mediating factor. Using a quantitative approach and Structural Equation Modelling (SEM) on 157 employees, the study develops a framework for enhancing employee outcomes. The results indicate that servant leadership has a positive impact on both performance and commitment, through direct and indirect channels. Work motivation proved to be a critical mediator, explaining 38.95% of the total effect of servant leadership on performance and 24.68% of the effect on commitment. The main contribution of this study is its integrated model, which explores the synergy between servant leadership and motivation within the bureaucratic and collectivist setting of Indonesian public enterprises. These findings strengthen existing motivation theories, while practically, they underscore the necessity for public organizations to adopt an approach that cultivates servant leaders and strengthens motivation through supportive systems. In summary, servant leadership and work motivation function together to improve performance and commitment. Future studies are encouraged to extend this model to other industries and use mixed-methods research for deeper contextual understanding.